Analisis Tingkat Kesesuaian Syariah Dalam Proses Produksi Pewangi “Fresh” Laundry Pada Roicool Cipta Mandiri - Faina, Lina (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the extent to which the conformity level of laundry fragrance products, what factors can affect the level of conformity of sharia in the laundry fragrance production process, as well as how the implementation of business licenses for laundry fragrance product home industries is enforced. This research is a field research with a qualitative approach using a qualitative paradigm of social construction phenomenology. The data collection techniques are carried out by observation, interviews, and documentation. While the object of this research is the owner of a home business or home industry